POLA PENYEBARAN KANTONG SEMAR (Nepenthes tentaculata Hook.F) DI GUNUNG ROREKAUTIMBU KAWASAN TAMAN NASIONAL LORE LINDU - Natalia, Dina; Umar, Husain; Sustri, Sustri (Universitas Tadulako, 2014)
Nepenthes tentaculata Hook.f. Â is one from nine Nepenthes species founded in Sulawesi island. It is a genus carnivorous plants that popularly known as tropical pitcher plants. Study on the diversity of kantong semar (Nepenthes, spp) was conducted in mount Rorekautimbu, Lore Lindu National Park, Central Sulawesi. The study was conducted on July through August 2013. The procedures of data collection were including species collection in the field, make up herbariums, and observation of Nepenthes tentaculata Hook.f. by using transect method along tracking lines. Seven lines (50m in length) were made in the field. The results show that distribution pattern of Nepenthes tentaculata Hook.f. at all lines in Rorekautimbu mount were in concentric form that influenced by some factors. Furthermore, the highest of Morisitas index was founded at transect VII with value 1.07, while the lowest was founded at transect V and VI with value 1.01. Keywords: Distribution, Pattern, Nepenthes tentaculata Hook. f., Mount Rorekautimbu, Lore Lindu National Park.